Analisis Kepuasan Pengguna SLiMS Menggunakan Metode SUS : System Usability Scale - Siwi Pelita Amini; Tata Sutabri (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
User satisfaction in information systems is a term used to describe how satisfied or dissatisfied users are when using a particular information system. User satisfaction includes how the information system meets the needs, expectations, and preferences of users in carrying out activities or achieving desired goals. User satisfaction is very important because it has a direct impact on the performance and success of information systems in organizations. The results of this study when viewed from Acceptability, Grade Scale and Adjective Rating are matched with the calculation of 50.5, namely the level of user acceptance is included in the marginal low category, the level of grade scale is included in the F category and the adjective rating is included in the ok-good category. According to the provisions of the conclusions that have been obtained, it can be concluded that users still experience difficulties when using SLiMS.